2017
DOI: 10.1007/s11748-017-0838-1
|View full text |Cite
|
Sign up to set email alerts
|

Japanese perspective in surgery for thoracoabdominal aortic aneurysms

Abstract: Our concept of spinal cord protection, which was based on selective intercostal reconstruction while maximizing spinal cord collateral blood flow, seems justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Improved results of open repair for TAAA have been reported for the combination of several important strategies including distal aortic perfusion, moderate hypothermia, sequential aortic clamping, spinal monitoring, CSFD, visceral perfusion, and reconstruction of intercostal and lumbar arteries or AKA [3]- [15]. Despite employing all the above-listed strategies, the outcomes of TAAA operations performed in our hospital before 2011 were quite discouraging, with an 11.1% rate of in-hospital mortality and an 8.3% incidence of postoperative paraplegia among the 36 TAAA patients treated during that period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved results of open repair for TAAA have been reported for the combination of several important strategies including distal aortic perfusion, moderate hypothermia, sequential aortic clamping, spinal monitoring, CSFD, visceral perfusion, and reconstruction of intercostal and lumbar arteries or AKA [3]- [15]. Despite employing all the above-listed strategies, the outcomes of TAAA operations performed in our hospital before 2011 were quite discouraging, with an 11.1% rate of in-hospital mortality and an 8.3% incidence of postoperative paraplegia among the 36 TAAA patients treated during that period.…”
Section: Discussionmentioning
confidence: 99%
“…SCI is one of the most serious complications of TAAA surgery, severely affecting prognosis and quality of life. Although many preventive and therapeutic approaches have been proposed [3]- [15], the risk of SCI-related paraplegia cannot be fully eliminated because its underlying mechanism is multifactorial. Some clinical and experimental reports have suggested that augmentation of systemic blood pressure during spinal cord ischemia increases spinal cord blood flow and decreases the risk of postoperative neurologic complications [16] [17] [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ann Thorac Surg 2019;107:733-9) Ó 2019 by The Society of Thoracic Surgeons D elayed paraplegia is a devastating complication after thoracoabdominal aortic interventions. The incidence of paraplegia ranges from 5% to 20% [1][2][3]. Although various surgical strategies have advanced, there is no widely recognized pharmacotherapy available to protect the spinal cord.…”
mentioning
confidence: 99%
“…(Ann Thorac Surg 2018;106:1751-8) Ó 2018 by The Society of Thoracic Surgeons P araplegia after thoracoabdominal aortic repair remains a devastating complication, occurring in 7% to 20% of thoracoabdominal interventions [1,2]. Despite the advancement of surgical strategies to protect the spinal cord, no pharmacologic therapy currently available has been shown to effectively prevent this complication [3].…”
mentioning
confidence: 99%